Mean field and pairing properties in the crust of neutron stars - Montani, Fernando Fabián (2004)
Properties of the matter in the inner crust of a neutron star are investigated in a Hartree-Fock plus BCS approximation employing schematic effective forces of the type of the Skyrme forces. Special attention is paid to differences between a homogenous and inhomogeneous description of the matter distribution. For that purpose self-consistent Hartree-Fock calculations are performed in a spherical Wigner-Seitz cell. The results are compared to predictions of corresponding Thomas-Fermi calculations. The influence of the shell structure on the formation of pairing correlations in inhomogeneous matter are discussed.